A critical imbalance in US trade: The US balance of payments, international indebtedness, and economic policy - Wynne Godley (Levy Economics Institute of Bard College, 1995)
According to Wynne Godley, the significance of the deficit in the United States' balance of payments has been underestimated in both public policy and academic discussions, despite the fact that American markets are increasingly dominated by foreign manufacturers. Godley analyzes the problem posed by the current balance of payments deficit. Breaking down the current account into its component parts, he traces the cause of the deficit. He refutes the arguments of other economists that the balance of payments deficit is self-correcting, unimportant, or the result of other domestic forces (namely, too low a level of national saving), and outlines policy approaches to solving the problem. Godley notes that although the strategic problems posed are specific to this country and the United States may have to take unilateral action to solve them, the problems have arisen because there is no significant international regulation of the system as a whole. Inherent flaws have developed in the system of international production, trade, and payments as that system has expanded and become increasingly deregulated. All the difficulties that exist, or that are foreshadowed in this brief, would be best resolved by energetic international cooperation, of which there is at present little sign.
Keywords: 330